Cellular responses induced by environmental stress factors in Arctic Seabird chicks : Responses of the antioxidant defense system and autophagic lysosomal processes related to contaminant exposure and food restriction - Hegseth, Marit Nøst (2011)
The papers of this thesis are not available in Munin: 1. Marit Nøst Hegseth, Lionel Camus, Lisa Bjørnsdatter Helgason, Raffaella Bocchetti, Geir Wing Gabrielsen and Francesco Regoli: 'Hepatic antioxidant responses related to levels of PCBs and metals in chicks of three Arctic seabird species', Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology (2011) 154: 28-35. Available at http://dx.doi.org/10.1016/j.cbpc.2011.02.008 2. Marit Nøst Hegseth, Lionel Camus, Stefania Gorbi, Francesco Regoli and Geir Wing Gabrielsen: 'Effects of exposure to halogenated organic compounds combined with dietary restrictions on the antioxidant defense system in herring gull chicks', Science of the Total Environment (2011) 409 (14):2717-24. Available at http://dx.doi.org/10.1016/j.scitotenv.2011.04.004 3. Marta K. Jansen, Marit Nøst Hegseth, Raffaella Bocchetti, Francesco Regoli, Geir W. Gabrielsen and Lionel Camus: 'Impact of Halogenated Organic Contaminant Exposure and Fasting on Antioxidant Defence System on the Kidney of Herring Gull Chicks' (manuscript) 4. Marit Nøst Hegseth, Francesco Regoli, Stefania Gorbi, Raffaella Bocchetti, Geir Wing Gabrielsen and Lionel Camus: 'Lysosomal and lipid-associated parameters in the livers of three species of arctic seabird chicks : Species differences and relationships with contaminant levels', Marine Pollution Bulletin (2011) 62(8): 1652-60. Available at http://dx.doi.org/10.1016/j.marpolbul.2011.06.011 5. Marit Nøst Hegseth, Stephania Gorbi, Raffaella Bocchetti, Geir Wing Gabrielsen, Francesco Regoli and Lionel Camus: 'Effects of contaminant exposure and food restriction on hepatic lysosomal and lipid associated parameters in Herring gull chicks' (submitted manuscript to Environmental Research) This PhD study has investigated how two commonly occurring environmental stress factors in the Arctic (periods with little food and exposure to halogenated organic contaminants) have had an impact on two important cellular defense mechanisms in Arctic seabirds. The antioxidant ...